Performance of Soil Biogrouting as a Subgrade Material of the Road Pavement - Widjajakusuma, Jack; Waruwu, Aaazokhi; Kusnadi, Yulia Yunita; Lujaya, Jason; Wibowo, Kevin Aprilio (Civil Engineering Journal, 2025)
Soft clay subgrade is unsuitable for road pavement because it has low bearing capacity and CBR value. Therefore, the soil needs stabilization, but with a sustainable stabilization method. One of these methods is biogrouting, namely grouting, which uses bacteria. Thus, the main objective of this study was to determine the performance of Bacillus subtilis and Bacillus amyloliquefaciens bacteria in stabilizing the soil. The performance of these bacteria was quantified by the CBR value and soil-bearing capacity experimentally in a laboratory model test with each soil thickness of 0-30 cm. The CBR value of the soil improved by the biogrouting method by about 4 times the CBR value of untreated soil. The increase in bearing capacity was obtained about 4 times for treated soil with Bacillus subtilis and about 5 times for treated soil with Bacillus amyloliquefaciens. The layer thickness significantly improves the performance of the subgrade at a layer thickness of 20 cm. The new result of this study is that both bacteria are native Indonesian bacteria, so they are suitable for use in Indonesia. In addition, Bacillus amyloliquefaciens has never been used in research to increase soil-bearing capacity.